MINAT DAN KETERTARIKAN MASYARAKAT SOLO TERHADAP PERMAINAN GOARA-GOARA - Slamet Santoso (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
The aim of this research is to analyze the Solo community's interest in the game Goara-Goara. This research method uses a mixture (mixed methods). The sample in this study consisted of 50 people consisting of 45 men and 5 women aged 17-19 years. The research instruments used video recordings, documentation studies, questionnaires and interviews. The data collection technique uses Google forms and is processed using descriptive statistics. The results of research on the interests and interests of the Solo community towards the game of goara-goara show the following; 1). 90% of respondents stated that the Goara-Goara game model which was made like a circuit and had lots of posts made it more interesting. 2). 40% of respondents stated that the most difficult post was post 6, namely bamboo stilts. 3). 100% of respondents stated that post 4 of the suda manda/engklek game was the easiest. 4) 98% stated that they were ready to play the goara-goara game again in their area. 5) All respondents (100%) stated that this goara-goara game is worthy of being published to the wider community. There is high public enthusiasm and interest in playing the traditional game packaged through the goara-goara game, because the game is more interesting, challenging, able to increase strength, agility, endurance, balance and accuracy. Based on this, it can be concluded that the Solo community's interest in playing goara-goara is very high